2018
DOI: 10.1103/physrevphyseducres.14.020104
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Rasch modeling of two-tier multiple choice test: A case study using Lawson’s classroom test of scientific reasoning

Abstract: Assessment instruments composed of two-tier multiple choice (TTMC) items are widely used in science education as an effective method to evaluate students' sophisticated understanding. In practice, however, there are often concerns regarding the common scoring methods of TTMC items, which include pair scoring and individual scoring schemes. The pair-scoring method is effective in suppressing "false positives" at the cost of missing possible middle states of progression of student understanding. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 51 publications
4
43
0
3
Order By: Relevance
“…Students might implicitly know that the red light was not a factor, and then primarily focused on the influential factor (the gravity) in their explanations. This also agrees with many two-tier assessment studies which have demonstrated that knowing is easier than reasoning [34,41].…”
Section: B Qualitative Analysis Of Q11-12 and Q13-14supporting
confidence: 79%
See 3 more Smart Citations
“…Students might implicitly know that the red light was not a factor, and then primarily focused on the influential factor (the gravity) in their explanations. This also agrees with many two-tier assessment studies which have demonstrated that knowing is easier than reasoning [34,41].…”
Section: B Qualitative Analysis Of Q11-12 and Q13-14supporting
confidence: 79%
“…While the two-tier test was originally developed as an effective alternative of the traditional multiple-choice test to suppress the possible false positive [34,42,57], it has been unclear as to how to quantify the likelihood of false positives in TTMC tests. The method of analyzing inconsistent response patterns described in this paper provides a practical means to quantitatively evaluate the probabilities of possible false positives and negatives, which can be used as evidence for establishing the validity of two-tier tests.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, nearly all FCI items showed reasonable item parameters. In recent research and development, the use of the IRT family of analysis methods has gained popularity in PER, especially in the area of assessment development and validation [22][23][24][25]. For example, following the Rasch modeling procedures of assessment development [20], Mešić et al applied the Rasch model to develop the wave optics item bank [22].…”
Section: Analyzing Cis Using Item Response Theorymentioning
confidence: 99%